The Role of Teachers in Increasing Interest in Learning Arabic in Madrasah Aliyah 6 Aceh Besar - Yulia Maisari; Nurhalimah (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Madrasah Aliyah Negri 6 Aceh Besar has one of the compulsory classes, namely Arabic language classes, but many students still have difficulty following Arabic language classes. Therefore, the role of the teacher is very important to increase students' interest in learning Arabic, because with the role of the teacher, students will be more active and easier to follow the learning process. This research was chosen based on the nature of the material in the form of direct field observations and real events accompanied by interviews and documentation. Based on the results of the study, researchers came to the conclusion that the role of Arabic language teachers is very important to increase interest in learning in students who are still bored with their learning activities. Teachers are motivators and drivers of student learning. If the teacher is not effective in teaching, students will be bored in participating in learning activities, so here the researcher takes the role of the teacher in educating students. interest in learning Arabic subjects so that students are not bored in learning.